Penerapan E-Commerce Berbasis Content Management System (CMS) Dengan Metode Business Model Canvas (BMC) Pada Toko Fajar Collection - Muhammad Ircham Zamroni; Anita Diana; Dwi Achadiani (Universitas Budi Luhur, 2022)
Fajar Collection is an individual business store that sells various products such as school uniforms, Muslim clothing, and casual clothes. In the existing business processes at Fajar Collection, using social media in the process of online sales transactions using Facebook and WhatsApp. However, with the online transaction business process, there are several obstacles experienced by the Fajar Collection store, namely, it is difficult for customers to find out stock availability, because there is no stock availability information on Facebook and WhatsApp, so customers have to ask the sales staff about stock inventory. Another obstacle is that the product promotion process is less than optimal, causing old products to be sold and slow to get new potential customers. Another obstacle is difficult in processing sales report data, because it is still done in bookkeeping by looking at sales notes to be included in the sales report, thus allowing different recordings of sales numbers and less than optimal in knowing sales data. Based on these constraints, an e-commerce website was designed using the Business Model Canvas (BMC) approach. Analysis of the strengths and weaknesses of the e-commerce business using the BMC methodology. The system was developed using the Unified Modeling Language (UML) approach and a Content Management System (CMS) based website with WordPress using the woocommerce plugin. Then it is optimized by applying Search Engine Optimization (SEO) so that the site is on the first page of search engines, making it easier for customers to find the site. With the E-Commerce website, it will expand product sales promotions, and help customers who want to buy directly from the website. It is hoped that by utilizing this E-Commerce website, it will be easier for customers to process the purchase transactions in Fajar Collection.